Compressions in Ironic Headlines Referring to Politicians of the USA and Lithuania - Vengalienė, Dovilė (Verbum, 2013)
In the article the scientific model of conceptual blending (developed by Mark Turner and Gilles Fauconnier) is applied to the analysis of ironic headlines. It is argued that irony’s ability to make use of this mechanism partially accounts for the use of ironic references in news discourse. Irony is used as a means to reveal the compressions created via blending. An ironist employs the rules of blending to present a variety of eye-catching and brief headlines that contain compressions of Time, Space, Part-Whole, Role-Value, Intentionality, and Analogy/Disanalogy that are compressed into Uniqueness. The multiple compressions of an ironic reference do not only enable the ironist to communicate complex ideas and implications at the scale of human understanding but also facilitate the economy of space (i.e. the complex conceptual integration networks operate in a way that brings elements from a variety of mental input spaces into one blend). An overview of the Vital Relations and their compressions is supported by a number of ironic news headlines collected from popular Lithuanian and American online news websites.
Keywords: conceptual blending; irony; compressions; mental spaces